Meralgia paresthetica caused by inguinal lymphadenopathy related to tinea pedis infection: A case report - YOLCU, GÜNAY; YAĞCI, İLKER (My University, 2021)
Mechanical compression at any point along the lateral femoral cutaneous nerve (LFCN) may result in meralgia paresthetica (MP). A 54-year-old male patient presented with pain and tingling on the anterolateral side of thigh. After excluding other causes of pain radiating to legs, he was diagnosed with MP. Inguinal lymphadenopathy which caused the compression of LFCN was found on ultrasonographic examination. Tinea pedis infection was also identified during the detailed investigation for lymphadenopathy. Associated MP symptoms partially resolved immediately after ultrasound-guided LFCN block and a complete recovery was achieved after the treatment of tinea pedis.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Rehabilitation; Meralgia paresthetica; Tinea pedis; Ultrasound